Identification of enterotoxigenic Escherichia coli isolates with enzyme-labeled synthetic oligonucleotide probes. - Medon, P P (1988)
Commercially available kits containing alkaline phosphatase-labeled oligonucleotide probes for Escherichia coli heat-stable enterotoxins (STI-H, STI-P, and STII) and the heat-labile enterotoxin were compared with bioassays and radiolabeled recombinant DNA probes to identify enterotoxigenic E. coli from 100 clinical isolates. There was very good agreement between the three methods.